How should minimally important change (MIC) scores for the Patient Oriented Eczema Measure (POEM) be interpreted?: a validation using varied methods - Howells, Laura; Ratib, Sonia; Chalmers, J.R.; Bradshaw, Lucy; Thomas, K.S. (Wiley, 2018)
Background